Myth and history in Celtic and Scandinavian traditions - Lyle, Emily B. (The early medieval North Atlantic, 2021)
Frontmatter -- Contents -- Preface -- Introduction -- Celtic Tradition -- 1 The Nature of the Fomoiri: The Dark Other in the Medieval Irish Imagination -- 2 Tuatha Dé and Fomoiri in Cath Maige Tuired -- 3 Exploring Cath Maige Tuired through the Concept of Hybridity -- 4 How Time Flies in the Cath Maige Tuired -- 5 The Idols of the Pagan Irish in the Medieval Literary Imagination -- 6 Myth as a Historical Resource : The Case of Orgain Denna Ríg (The Destruction of Dinn Ríg) -- 7 Hagiography as Political Documentation : The Case of Betha Beraigh (The Life of St Berach) -- Scandinavian Tradition -- 8 Baldr’s Achilles’ Heel? About the Scandinavian Three-God B-Bracteates -- 9 The Cult of Óðinn in the Early Scandinavian Warrior Aristocracy -- 10 Myth to History in Saxo -- 11 The Scylding Dynasty in Saxo and Beowulf as Disguised Theogony -- 12 Loki the Slandered God? Selective Omission of Skaldic Citations in Snorri Sturluson’s Edda -- 13 Ymir, Baldr, and the Grand Narrative Arc of Mythological History -- Index